2021
DOI: 10.1186/s12970-021-00472-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food sources of nitrate, polyphenols, L-arginine and L-citrulline on endurance exercise performance: a systematic review and meta-analysis of randomised controlled trials

Abstract: Background Increasing nitric oxide bioavailability may induce physiological effects that enhance endurance exercise performance. This review sought to evaluate the performance effects of consuming foods containing compounds that may promote nitric oxide bioavailability. Methods Scopus, Web of Science, Ovid Medline, EMBASE and SportDiscus were searched, with included studies assessing endurance performance following consumption of foods containing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 209 publications
(117 reference statements)
0
18
0
Order By: Relevance
“…Polyphenols may enhance NO production via the eNOS expression pathway and activity, according to previous literature data; these molecules also promote NO bioavailability via their antioxidant effects, which protect NO from breakdown by ROS. [33] Quercetin has potent immunostimulatory properties and has been shown to reduce the effects of aging in immune cells. While also reducing oxidative stress in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols may enhance NO production via the eNOS expression pathway and activity, according to previous literature data; these molecules also promote NO bioavailability via their antioxidant effects, which protect NO from breakdown by ROS. [33] Quercetin has potent immunostimulatory properties and has been shown to reduce the effects of aging in immune cells. While also reducing oxidative stress in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sellitto et al [ 68 ] reported that antioxidant supplementation may hinder the Role of exercise training as a natural activator of sirtuin 1 (SIRT1) which is activated by polyphenols antioxidants. On the other hand, highly trained endurance athletes did not benefit from consuming nitrate-rich foods but might have benefited from polyphenol consumption [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were congruent with a previous study whereby PS increased NO production in hydrogen peroxide-induced endothelial cells by increasing eNOS mRNA expression, protein level and activity ( Ugusman et al, 2010 ). Owing to the antioxidative activity of PS, PS may increase the bioavailability of NO ( Mohd Zainudin et al, 2019 ), as an antioxidant protects NO from the breakdown by ROS ( d’Unienville et al, 2021 ). In SHR, oral administration of a potent antioxidant, lazaroid, improves NO bioavailability and reduces blood pressure ( Sorriento et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%